Multicentric Castleman's disease in a renal allograft recipient: a case report and literature review. Issue 2 (February 2020) - Lin, Jinwen; Yu, Shiping; Wang, Rending; Chen, Jianghua
Giant lymph node hyperplasia is the main symptom of Castleman's disease (CD), which is a rare and easily overlooked lymphoproliferative disease that mimics both benign and malignant lesions. Several cases of CD after renal transplantation have been reported in the literature. A 43-year-old man was admitted to our medical center with high serum globulin levels after receiving a living donor kidney transplant. A lymph node biopsy raised suspicion for multicentric CD. Because of the poor therapeutic effect of reduction of immunosuppression, the patient was treated with CHOP chemotherapy comprising four cycles of monthly cyclophosphamide (750 g/m 2, day 1), vincristine (1.4 g/m 2, day 1), doxorubicin (50 g/m 2, day 1), and prednisone (60 mg/m 2, daily). Following the treatment, his serum globulin levels decreased to the normal range. At the 2-year follow-up examination, the abdominal, axillary, and inguinal lymph nodes had significantly decreased in size. Without a pathological diagnosis, multicentric CD after renal transplantation can be easily ignored and misdiagnosed. If the clinical signs cannot be relieved by minimizing the dose of common immunosuppressants, the CHOP regimen may be a better option. Biological agents may be added in patients with positive immunohistochemistry staining and good economic conditions.